PENINGKATAN KUALITAS PERKULIAHAN FISIOLOGI TUMBUHAN MELALUI LESSON STUDY DI JURUSAN BIOLOGI FMIPA UM - Herawati Susilo; Balqis Balqis (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Since three years ago Plant Physiology lecture has been using a model of learning Reading, Questioning, and Answering System (RQA), but the results are still not satisfactory. Three open classes of Lesson Study (LS) has been implemented to improve the lecture on April 4, 7, and 14,  2014 by the LS Team consisting of three lecturers and four assistant lecturers. The input for improving the teaching and learning process of lecture conducted as a result of reflection before and after three open classes covers additional tasks preparing a concept map or mind map tasks besides RQA, the improved form of  power point presentation,  improved mastery of material by the  presenters, query answering written questions in the Chapter Review  that the material covered is more substantial. Presenters should also display images related to the  material being discussed, request that the student submit the RQA power point at the beginning of lecture, and gave a rebuttal that is not a technical issue but a substantial concerns, as well as write and collect lecture notes at the end of the course. The results showed an improvement in the learning  processes and increased student engagement in learning. Plant Physiology improvement of learning outcomes is still not satisfactory . Keywords: improvement, quality of lectures, Plant Physiology , Lesson Study , FMIPA UM